Solve for y
y=-1
y=17
Graph
Share
Copied to clipboard
y^{2}-16y+64-81=0
Subtract 81 from both sides.
y^{2}-16y-17=0
Subtract 81 from 64 to get -17.
a+b=-16 ab=-17
To solve the equation, factor y^{2}-16y-17 using formula y^{2}+\left(a+b\right)y+ab=\left(y+a\right)\left(y+b\right). To find a and b, set up a system to be solved.
a=-17 b=1
Since ab is negative, a and b have the opposite signs. Since a+b is negative, the negative number has greater absolute value than the positive. The only such pair is the system solution.
\left(y-17\right)\left(y+1\right)
Rewrite factored expression \left(y+a\right)\left(y+b\right) using the obtained values.
y=17 y=-1
To find equation solutions, solve y-17=0 and y+1=0.
y^{2}-16y+64-81=0
Subtract 81 from both sides.
y^{2}-16y-17=0
Subtract 81 from 64 to get -17.
a+b=-16 ab=1\left(-17\right)=-17
To solve the equation, factor the left hand side by grouping. First, left hand side needs to be rewritten as y^{2}+ay+by-17. To find a and b, set up a system to be solved.
a=-17 b=1
Since ab is negative, a and b have the opposite signs. Since a+b is negative, the negative number has greater absolute value than the positive. The only such pair is the system solution.
\left(y^{2}-17y\right)+\left(y-17\right)
Rewrite y^{2}-16y-17 as \left(y^{2}-17y\right)+\left(y-17\right).
y\left(y-17\right)+y-17
Factor out y in y^{2}-17y.
\left(y-17\right)\left(y+1\right)
Factor out common term y-17 by using distributive property.
y=17 y=-1
To find equation solutions, solve y-17=0 and y+1=0.
y^{2}-16y+64=81
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
y^{2}-16y+64-81=81-81
Subtract 81 from both sides of the equation.
y^{2}-16y+64-81=0
Subtracting 81 from itself leaves 0.
y^{2}-16y-17=0
Subtract 81 from 64.
y=\frac{-\left(-16\right)±\sqrt{\left(-16\right)^{2}-4\left(-17\right)}}{2}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 1 for a, -16 for b, and -17 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
y=\frac{-\left(-16\right)±\sqrt{256-4\left(-17\right)}}{2}
Square -16.
y=\frac{-\left(-16\right)±\sqrt{256+68}}{2}
Multiply -4 times -17.
y=\frac{-\left(-16\right)±\sqrt{324}}{2}
Add 256 to 68.
y=\frac{-\left(-16\right)±18}{2}
Take the square root of 324.
y=\frac{16±18}{2}
The opposite of -16 is 16.
y=\frac{34}{2}
Now solve the equation y=\frac{16±18}{2} when ± is plus. Add 16 to 18.
y=17
Divide 34 by 2.
y=-\frac{2}{2}
Now solve the equation y=\frac{16±18}{2} when ± is minus. Subtract 18 from 16.
y=-1
Divide -2 by 2.
y=17 y=-1
The equation is now solved.
y^{2}-16y+64=81
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
\left(y-8\right)^{2}=81
Factor y^{2}-16y+64. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(y-8\right)^{2}}=\sqrt{81}
Take the square root of both sides of the equation.
y-8=9 y-8=-9
Simplify.
y=17 y=-1
Add 8 to both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}